Association of gut microbiome and metabolites with onset and treatment response of patients with pemphigus vulgaris - Wang, Yiyi; Xia, Xuyang; Zhou, Xingli; Zhan, Tongying; Dai, Qinghong; Zhang, Yan; Zhang, Wei; Shu, Yang; Li, Wei; Xu, Heng (Frontiers in Immunology, 2023)
Background: Gut dysbiosis and gut microbiome-derived metabolites have been implicated in both disease onset and treatment response, but this has been rarely demonstrated in pemphigus vulgaris (PV). Here, we aim to systematically characterize the gut microbiome to assess the specific microbial species and metabolites associated with PV. Methods: We enrolled 60 PV patients and 19 matched healthy family members, and collected 100 fecal samples (60 treatment-naïve, 21 matched post-treatment, and 19 controls). Metagenomic shotgun sequencing and subsequent quality control/alignment/annotation were performed to assess the composition and microbial species, in order to establish the association between gut microbiome with PV onset and treatment response. In addition, we evaluated short-chain fatty acids (SCFAs) in PV patients through targeted metabolomics analysis. Results: The diversity of the gut microbiome in PV patients deviates from the healthy family members but not between responder and non-responder, or before and after glucocorticoid treatment. However, the relative abundance of several microbial species, including the pathogenic bacteria (e.g., Escherichia coli) and some SCFA-producing probiotics (e.g., Eubacterium ventriosum), consistently differed between the two groups in each comparison. Escherichia coli was enriched in PV patients and significantly decreased after treatment in responders. In contrast, Eubacterium ventriosum was enriched in healthy family members and significantly increased particularly in responders after treatment. Consistently, several gut microbiome-derived SCFAs were enriched in healthy family members and significantly increased after treatment (e.g., butyric acid and valeric acid). Conclusions: This study supports the association between the gut microbiome and PV onset, possibly through disrupting the balance of gut pathogenic bacteria and probiotics and influencing the level of gut microbiome-derived SCFAs. Furthermore, we revealed the potential relationship between specific microbial species and glucocorticoid treatment.